FACTORS INFLUENCING THE WILLINGNESS TO WALK TO THE BUS STOPS IN PENANG ISLAND - Abdul Sukor, Nur Sabahiah; Muhammad Fisal, Siti Fadhlina (PLANNING MALAYSIA, 2018)
This study, investigates pedestrians’ ‘willingness to walk’ to Rapid Penang bus stops in Penang Island. Parameters, such as socio-demographics, walking distance and walking time, were examined to determine factors that influence ‘willingness to walk’. Questionnaire surveys were used to collect the data from 400 participants. The data was analysed using multiple regression analysis through the ‘Statistical Package for the Social Sciences’ (SPSS). Analysis of determinant factors was split into two dependent variables. Firstly, the willingness to walk based on current condition, and secondly, the willingness to walk, if improvements to environment and infrastructure were made to the bus stops. The results showed that socio-demographic factors, such as walking distance, walking time and trip purpose would likely to influence the pedestrians’ ‘willingness to walk’. This study also identified the maximum, minimum, and average distances walked by a pedestrian to reach the bus stops (as well as the willingness travel time.) The outcome of this study will contribute to better planning of transportation system in Penang Island especially on the Penang Transport Master Plan (PTMP) projects.